CIAT Genetic Resources Unit: Annual Reports: 1982-1997 - International Center for Tropical Agriculture (1982)
Project is referred to as SB-01 (in 1997 and 2001) and SB-2 "Conservation and use of Tropical Genetic Resources" in 2006.